Industry 4.0: a critical reflection on its impacts on family farming - Apablaza, Gustavo Federico (Frontiers in Political Science, 2024)
This paper identifies groups of disruptive technologies within the framework of Industry 4.0 that can advance and integrate sustainable rural development processes. Technological advances are described and an analysis is made of the possible positive and negative effects of their implementation in family and sustainable agriculture in Brazil. To support family farming's innovative potential here, the restructuring of existing power relations and higher levels of participation, training, and education are required.